Pemetaan struktur kelembagaan food hub pada rantai pasok hortikultura sebagai pusat pangan daerah yang berkelanjutan - Rudi Kresna; Wawan Gunawan; Dini Siti Hanifah; Ajat Sudrajat; Fairuz Labibah; Gabriel Toen Toen Sahat Tua Situngkir (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Food supply chain problems remain a critical issue that has the potential to disrupt food security and resilience, especially in the horticulture sub-sector. One strategic approach to addressing supply chain issues is through comprehensive role of food hub. Food hub serve as centers that can integrate various production services and distribution facilities, making them the optimum solution for supply chain problems. They require the role and function of professional institutions as the key to strengthening governance, multi-actor coordination, and the provision of policies to achieve the objectives and sustainability of food hubs. Therefore, a review of existing institutional conditions is necessary as a preliminary assessment to develop an appropriate institutional model for food hub, particularly in Bandung Regency as the location under study. A prescriptive approach to the institutional aspects of food hubs was conducted using the Institutional Analysis and Development (IAD) Framework, where research development was tailored to the relevance of local needs. Data and information were collected using qualitative methods with various techniques. Based on the results, revealed that the existing conditions of the food hub showed low participation from relevant actors and weak collaboration between communities and local policy makers. Food hub activities have not been running efficiently. It is necessary to strengthen the roles of relevant stakeholders, collaboration, and integration to strengthen the institutional functions of food hubs. Furthermore, to ensure that these functions are appropriate, it is necessary to increase human resource capacity, monitor and evaluate business planning, and provide synergistic regulations and policies.